Digital Public Sentiment Toward Out-of-Wedlock Pregnancy and Its Implications for Health Policy in Indonesia - Herliana Riska; Bambang Widoyono; Dewi Sartika; Nur Khasanah (Indonesian Health Issue, 2026)
Background: Unmarried pregnancy in Indonesia remains closely associated with gendered moral norms and social stigma, which may limit women’s access to equitable maternal health services. Digital platforms such as YouTube function as public arenas where these norms are reproduced, contested, and potentially influence informal policy environments. Purpose: This study aims to analyze digital public sentiment toward unmarried pregnant women and to examine its implications for gender-responsive and intersectional maternal health policy in Indonesia. Methods: A qualitative descriptive study was conducted using content analysis of publicly available YouTube comments posted between January 2024 and 2026. Comments from highly engaged videos discussing unmarried pregnancy were anonymized and categorized into negative, positive, and neutral sentiment groups. Descriptive statistics were used to present proportional distributions. Results: Negative sentiment dominated the discourse (47.25%), followed by positive sentiment (39.32%) and neutral sentiment (13.44%). Although moral judgment and stigma remain prominent, a substantial proportion of comments express empathy and support. Conclusions: Digital public sentiment reflects persistent gender stigma surrounding unmarried pregnancy, alongside emerging supportive narratives. Integrating intersectional and rights-based approaches aligned with WHO recommendations is essential to strengthen inclusive maternal health policy and ensure equitable access to care for all women, regardless of marital status.